Enhanced Brain Source localization using Multimodal signal Fusion - Chaari, Anas (2025)
A Master of Science thesis in Biomedical Engineering by Anas Chaari entitled, “Enhanced Brain Source localization using Multimodal signal Fusion”, submitted in December 2025. Thesis advisor is Dr. Hasan Al Nashash and thesis co-advisor is Dr. Hasan Mir. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).